Ketentuan Administrasi Perbankan Syariah Serta Jenis Kegiatan Usaha Dan Larangan Dalam Bank Syariah - Wahid, St. Hadijah; Yunita, Rahma; Amelia, Nurul; Indah, Mega Sasmita; Adrianto, Adrianto; Salmi, Salmi; Destiani, Destiani; Haerani, Haerani; Miranda, Misra (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
This article comprehensively discusses the administrative provisions of Islamic banking and the types of business activities permitted within the Islamic banking system in Indonesia. Administrative provisions are a crucial component in ensuring that every banking institution’s activities are carried out in accordance with Islamic principles, from determining administrative fees and fulfilling administrative requirements to the types of financial products that comply with provisions free from riba, gharar, and maisyir. This study also examines the legal basis governing Islamic banking operations, which originates from the 1945 Constitution, banking laws, and specific regulations such as Law Number 21 of 2008 concerning Islamic Banking. Using a literature review method, this article concludes that administrative provisions not only serve to maintain Islamic compliance but also serve as a governance instrument that enhances public trust. The integration of regulations, Islamic contract mechanisms, and transparency of administrative costs strengthens Islamic banking’s position as part of a modern financial system that is safe, sound, and Islamically compliant